THE PRINCIPLE OF EFFICIENCY IN ADMINISTRATIVE PROCEDURE – DILLEMAS AND CHALLENGES - Shumanovska Spasovska, Ivana; Davitkovska, Elena; Piperkova, Irina (Economic Institute , Ss Cyril and Methodius University in Skopje, 2022)
This paper elaborates the issues referring to the legal regulation of the principle of efficiency, its meaning, as well as application of this principle. The aim of this paper is to analyze the legal framework that defines the principle of efficiency in the administrative procedure in the Republic of North Macedonia, present an empirical analysis of data from the work of the State Commission for Decision-making in Administrative Procedure and Labor Relations Procedure in Second Instance, identify the factors that influence the consistent application of this principle, as well as offer recommendations for an improved application of the principle. The authors believe that although measures and activities that contribute to achieving the principle of efficiency in the administrative procedure have been applied, there are more measures that need to be taken, i.e., actions that would strengthen institutional c
Keywords: administrative procedure, efficiency, effectiveness, complaint, principles in administrative procedure